Identification of hub genes associated with osteoporosis development by comprehensive bioinformatics analysis - Deng, Yuxuan; Wang, Yunyun; Shi, Qing; Jiang, Yanxia (Frontiers in Genetics, 2023)
Osteoporosis (OP) is a systemic bone disease caused by various factors, including, the decrease of bone density and quality, the destruction of bone microstructure, and the increase of bone fragility. It is a disease with a high incidence in a large proportion of the world's elderly population. However, osteoporosis lacks obvious symptoms and sensitive biomarkers. Therefore, it is extremely urgent to discover and identify disease-related biomarkers for early clinical diagnosis and effective intervention for osteoporosis. In our study, the Linear Models for Microarray Data (LIMMA) tool was used to screen differential expressed genes from transcriptome sequencing data of OP blood samples which were downloaded from GEO database, and cluster Profiler was used for enriching analysis of differential expressed genes. In addition to the relevance of gene modules, clinical symptoms, and the most related module setting genes associated with diseases progression, we adapted Weighted Gene Co-expression Network Analysis (WGCNA) to screen and analyze the related pathways and relevant molecules. We used the Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) database to construct protein interaction network of key modules, and Cyto scape software was used to complete network visualization and screen of core genes in the network. Various plug-in algorithms of cyto Hubba were used to identify key genes of OP. Finally, correlation analysis and single-gene gene probe concentration analysis (GSEA) analysis were performed for each core gene. Results of a total of 8 key genes that were closely related to the occurrence and development of OP were screened out, which provided a brand-new idea for the clinical diagnosis and early prevention of OP. Quantitative real-time PCR was performed for validation，the expression levels of CUL1, PTEN and STAT1 gene in the OS group were signiﬁcantly higher than in the non-OS groups. Receiver operating characteristic analysis demonstrated that CUL1, PTEN and STAT1 displayed considerable diagnostic accuracy for OS .